Kampung Melayu Urban Design Study - Nurjalal, Muhamad; Pradini, Purnama Sakhrial (Peneliti.net, 2025)
Kampung Melayu is a densely populated residential area located on the banks of the Ciliwung River in East Jakarta, which has experienced organic growth without systematic spatial planning. This area faces various urban problems, such as irregular land use, a lack of green open spaces, narrow circulation, and environmental conditions that do not meet the principles of sustainable urban design. This study aims to identify the main issues in the physical structure of the area and formulate recommendations for its development using Hamid Shirvani's urban design theory, which includes eight elements: land use, building form and mass, circulation and parking, open spaces, pedestrian paths, supporting activities, signage and orientation systems, and area image. The methods used include field observations, spatial analysis, and review of regulations such as SNI 03-1733-2004, the Jakarta Capital City Regional Spatial Plan (RTRW), and Law No. 26 of 2007. The results revealed significant inconsistencies in most design elements, particularly in terms of circulation connectivity and the provision of public spaces. This study recommends micro-zoning-based planning, the revitalisation of open spaces, and the strengthening of local identity to achieve sustainable housing in densely populated urban areas.